Investigation of Obesity, Physical Activity and Self-Efficacy-Efficacy Levels in Primary School Students - Medine YILMAZ; Gamze AĞARTIOĞLU KUNDAKÇI; Gülçin UYANIK; Dilek ONGAN; Hatice YILDIRIM SARI; Nurdan AKAY; Ertan ALGÜL; Asaf YILDIRIM (Ahi Evran Medical Journal, 2022)
Purpose: The research was conducted to examine the obesity status, nutritional knowledge and behaviors, physical activity and selfefficacy levels of children aged 7-9 years.